Small mammal diversity and dynamics within Nigeria, with emphasis on reservoirs of the lassa virus. Issue 2 (17th February 2018) - Olayemi, Ayodeji; Obadare, Adeoba; Oyeyiola, Akinlabi; Fasogbon, Samuel; Igbokwe, Joseph; Igbahenah, Felix; Ortsega, Daniel; Günther, Stephan; Verheyen, Erik; Fichet-Calvet, Elisabeth
Abstract : Nigeria has a rich small mammal community, with several species implicated as carriers of zoonotic microbes such as the Lassa virus (LASV). We sought to elucidate the diversity and distribution of these animals (including known LASV reservoirs) geographically, habitat-wise and seasonally. Our DNA-assisted survey detected at least 19 small mammal species amongst 790 specimens. Diversity indices were similar between ecological zones and also between endemic and non-endemic areas for Lassa fever. Mastomys natalensis, the most renowned LASV host, was present in eight out of nine localities sampled. We also described the spatial occurrence of other known LASV hosts such as M. erythroleucus and Hylomyscus pamfi, including carriers of LASV-like arenaviruses such as Mus ( Nannomys ) spp. The most numerous rodents ( Mastomys natalensis, M. erythroleucus, and Praomys daltoni ) were captured mainly inside human dwellings. Reproductive activity occurred throughout the year, but led to population peaks for M. natalensis in the dry season and for M. erythroleucus and P. daltoni in the rainy season. Extensive geographic distribution of LASV rodent reservoirs, with population peaks in different seasons, shows that the risk of rodent-to-human transmission of LASV is greater than currently realized.